PENGARUH PENERAPAN GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN SEKTOR BASIC MATERIALS YANG TERDAFTAR DI ISSI (2020-2024) - Salsabila Dhiva Hauri; Usdeldi, Usdeldi; Marissa Putriana (Nusantara Hasana Journal, 2026)
This study aims to analyze the effect of green accounting implementation and environmental performance on firm value in the basic materials sector listed on the Indonesia Sharia Stock Index (ISSI) during the 2020–2024 period. Firm value is measured using Tobin’s Q ratio, green accounting is measured through environmental cost ratios, and environmental performance is measured using the PROPER rating. This research employs a quantitative approach using panel data regression analysis with EViews software. The research sample consists of 9 basic materials companies listed on ISSI during the observation period. The data are obtained from companies’ annual reports, sustainability reports, and PROPER reports. The results show that the implementation of green accounting has a positive and significant effect on firm value, while environmental performance does not have a significant effect on firm value. These findings indicate that investors still place greater emphasis on financial aspects than on environmental performance when assessing firm value.